“A” Business by Any Other Name: Firm Name Choice as a Signal of Firm Quality - McDevitt, Ryan C. (Journal of Political Economy, 2014)
This paper considers when a firm’s deliberately chosen name can signal meaningful information. The average plumbing firm whose name begins with A or a number receives five times more service complaints than other firms and also charges higher prices. Relatedly, plumbers with A names advertise more in the Yellow Pages and on Google, and doing so is positively correlated with receiving complaints. As the use of A names is more prevalent in larger markets, I reconcile these findings with a simple model in which firms have different qualities and consumers have heterogeneous search costs.